Building Solidarity and Cooperation Among Students Through the Gotong royong Program at the Indonesian School of Kuala Lumpur - Nainggolan, Daniel M; Nainggolan, Reynold; Hakim, Alexander Julianus; Abriansah, Mario; Acung, Warkis; Mohede, Herviyani Soedarmo (Teumulong: Journal of Community Service, 2024)
This project aims to explore and evaluate the effectiveness of the gotong royong program in fostering a sense of solidarity and cooperation among students at the Indonesian School of Kuala Lumpur. The method used in this community service project involves a direct immersion approach. Data was collected through participatory observation, in-depth interviews with students and teachers, and analysis of documentation related to the program's implementation. The results indicate that the gotong royong program is effective in strengthening social relationships among students. Active participation in gotong royong activities encourages students to help each other, work together, and build a sense of responsibility towards the school environment. In this context, the program not only improves school facilities but also creates positive emotional bonds among the participants. The implications of this project highlight the importance of expanding and sustaining gotong royong activities as an integral part of the school curriculum. Thus, schools can become environments that promote social values such as cooperation, solidarity, and care among students.